Spinal cord injury without radiological abnormality (SCIWORA) in a young female and pharmacological treatment option: a case report with review of literature - Sakan, Sanja; Pavlovic, Daniela Bandic; Baronica, Robert; Rukavina, Iva; Stern-Padovan, Ranka; Dobric, Ivan (International Journal of Research in Medical Sciences, 2017)
Acute spinal cord injury strikes labour active young and middle-aged population, especially men, and consequently usually results in difficult neurological sequel. Also disables normal quality of life and everyday functioning in these patients despite many available supportive measures. Spinal cord injury without radiological abnormality (SCIWORA) presents a great diagnostic challenge because radiological and computed tomography pictures are without visible pathology which would explain the new onset of the neurological deficit. For the first time we report a true spinal cord injury without radiological abnormality in the X-ray, computed tomography and magnetic resonance imaging in a young female manifested with moderate neurological deficit after the traffic accident. Although SCIWORA is very rare in adults, high level of suspicion in emergency department is advisable as the timely applied neuroprotective measures can prevent the onset of the neurological deficit. It is important to emphasize that emergency magnetic resonance imaging application is the diagnostic key. Albeit, the SCIWORA neurologic deficit can show up with a delay of four days after the spinal cord injury in a patient with a normal physical and radiological examination. Treatment of these patients is another challenge for every physician. In fact pharmacological treatment options are still in the experimental research phase. We can conclude that currently the neuroprotective measures of the acute spinal cord injury patient started in the emergency department regardless the radiological test findings represent the right and successful key treatment.